A hazard analysis methodology for the South African abattoir hygiene management system. Issue 12 (25th November 2014) - Govender, Reuben
Abstract : Purpose: – Hazard analysis critical control point (HACCP) systems facilitate a preventative and systematic approach to control food safety hazards through critical control points (CCPs). Hazards are prevented, eliminated or reduced to acceptable levels. The regulated South African abattoir hygiene management system (HMS) has adopted HACCP principles. Control points (CPs) represent the central feature of control within the HMS. However, there are no guidelines to conduct hazard analysis within the HMS. There is also no guideline to identify CPs. The purpose of this paper is to present a hazard analysis methodology that may be used at South African abattoirs to overcome these shortcomings. Design/methodology/approach: – A review of SANS 10330:2007 (HACCP) and the regulated HMS standards was undertaken. A generic HACCP plan was developed for a hypothetical bovine processing abattoir. A proposed hazard analysis methodology was used to analyse generic hazards to determine its significance. Thereafter, CCPs were identified using the CCP decision tree. This was done to enable meaningful comparison between HACCP-based CCPs and HMS-based CPs. The hazard analysis methodology suggested by the Codex Alimentarius Commission (CAC) namely, the two dimensional health risk assessment model used to assess the significance of food safety hazards was used as a benchmark. Findings: – The management of CPs in a HMS plan is similar to control contemplated in a HACCP plan. It was found that regulated CPs are not specifically stated as CPs, they need to be identified. Also, not all regulated CPs addressed the significant hazards that were identified using the proposed methodology in this paper. Managing only regulated CPs in the HMS plan may likely offer limited control over hazards. Therefore, hazards analysis is important to identify significant hazards and in turn, CPs that provide more comprehensive control within the HMS in addition to exercising control using only regulated CPs. It was observed that there are no decision criteria available to identify CPs, unlike HACCP. It was proposed that because CPs are defined similar to CCPs, that the CCP decision tree be used to identify CPs. Originality/value: – A hazard analysis methodology was proposed to develop the HMS as well as steps towards its development. A decision guideline was also presented to facilitate extracting CPs from regulations. Important definitions lacking in regulations, and relating to the HMS, have also been proposed in this paper. More robust HMSs may be developed by identifying regulated CPs as well as identifying them through hazard analysis.